Fabrication and Photovoltaic Properties of Silicon Solar Cells with Different Diameters and Heights of Nanopillars. Issue 2 (29th January 2013) - Liu, Jing; Zhang, Xinshuai; Ashmkhan, Marina; Dong, Gangqiang; Liao, Yuanxun; Wang, Bo; Zhang, Tianchong; Yi, Futing
Abstract Silicon nanopillars with average diameters from 200 to 900 nm and heights from 0.5 to 3 μm have been successfully fabricated by cesium chloride (CsCl) self‐assembly lithography and dry etching as antireflection layer for solar cells. The antireflection and photovoltaic characteristics for the structures of silicon nanopillars have been researched and show that the reflectivity, photovoltaic conversion efficiency (PCE), and external quantum efficiency (EQE) are greatly influenced by the average diameter and height of nanopillars. The nanopillars with small diameters and large heights can supress reflection, but have less‐favorable photovoltic properties because of greater surface recombination and a greater number of lattice defects. The lowest reflectivity was achieved for silicon nanopillars of 200 nm average diameter and 1.5 μm height, for which the reflectivity was below 5 % between the wavelengths of 400 and 1000 nm, and the solar cell with silicon nanopillars of 600 nm average diameter and 1.5 μm height exhibited the best solar cell performance with a PCE of 14.83 %, a short‐circuit current density (Jsc) of 36.89 mA cm−2, and an open‐circuit voltage (Voc) of 542 mV.